Ultrasound speckle tracking imaging measurement of endocardial longitudinal strain for evaluation of prognostic value of “new quadruple” therapy in patients with chronic heart failure - Tang, Man; Zeng, Yuwei; Zhao, Ping; Zhao, Qianlei (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to evaluate the effectiveness of the “new quadruple” therapy in chronic heart failure (CHF) patients with metabolic syndrome using 2D speckle tracking imaging (2D-STI) stratified strain imaging to measure endocardial longitudinal strain while exploring its underlying neuroendocrine mechanisms.Patients and methodsThe study retrospectively analyzed 158 patients with heart failure with reduced ejection fraction [HFrEF; left ventricular ejection fraction (LVEF) < 40%] treated with the “new quadruple” therapy (angiotensin receptor neprilysin inhibitor (ARNI), sacubitril/valsartan, dapagliflozin, bisoprolol, and spironolactone) for 8 weeks. Conventional ultrasound indices, left ventricular global longitudinal strain (LVGLS), and subendocardial longitudinal strain (LS) were measured pre- and post-treatment. Follow-up for 15 months recorded major adverse cardiac events (MACEs).ResultsThe 158 patients were divided into two groups: MACEs (n=25) and no MACEs (n=133). Univariate comparisons revealed significant differences between groups in coronary artery diameter stenosis percentage; admission LVEF and brain natriuretic peptide (BNP); LVGLS and subendocardial LS; post-treatment LVEF, LVGLS, and subendocardial LS, ΔLVGLS; and subendocardial ΔLS (P < 0.05). Multifactorial Cox regression modeling showed that coronary artery diameter stenosis, admission LVEF, BNP, subendocardial LS, post-treatment LVEF, and subendocardial LS were predictive factors for MACEs in HFrEF patients following “new quadruple” therapy (P < 0.05). ROC analysis indicates that post-treatment subendocardial LS predicts MACEs with an AUC of 0.871, which was significantly higher than other single metrics (P < 0.05).ConclusionsUsing 2D-STI layer-specific strain imaging to measure endocardial longitudinal strain serves as a significant non-invasive indicator in predicting MACEs during 1-year follow-up after “new quadruple” therapy in HFrEF patients with metabolic syndrome, highlighting substantial clinical applicability. Additionally, our findings suggest that the therapy may improve prognosis through the modulation of neuroendocrine mechanisms.